2016
DOI: 10.1089/aid.2016.0046
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylphosphatidylinositol Anchor Deficiency Attenuates the Production of Infectious HIV-1 and Renders Virions Sensitive to Complement Attack

Abstract: Human immunodeficiency virus type 1 (HIV-1) escapes complement-mediated lysis (CML) by incorporating host regulators of complement activation (RCA) into its envelope. CD59, a key member of RCA, is incorporated into HIV-1 virions at levels that protect against CML. Since CD59 is a glycosylphosphatidylinositol-anchored protein (GPI-AP), we used GPI anchor-deficient Jurkat cells (Jurkat-7) that express intracellular CD59, but not surface CD59, to study the molecular mechanisms underlying CD59 incorporation into H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…HIV-1 NL4-3 viral stock preparation and ex vivo infection. HIV-1 viral stock was prepared as described in our recent report [19]. In brief, viral DNA pNL4-3 (plasmid construct harbering full-length HIV genome NL4-3) was obtained from the NIH AIDS Reagent Program (Germantown, MD, USA).…”
Section: Mscv Retroviral Expressionmentioning
confidence: 99%
“…HIV-1 NL4-3 viral stock preparation and ex vivo infection. HIV-1 viral stock was prepared as described in our recent report [19]. In brief, viral DNA pNL4-3 (plasmid construct harbering full-length HIV genome NL4-3) was obtained from the NIH AIDS Reagent Program (Germantown, MD, USA).…”
Section: Mscv Retroviral Expressionmentioning
confidence: 99%
“…For example, Enk et al found that the herpes simplex virus (HSV)-1-encoded miR H8 could target the GPI anchoring pathway, which further reduced the expression levels of several immune-modulating proteins and finally enhanced viral spread and enabled evasion of elimination by natural killer cells [6]. Amet et al demonstrated that a deficiency of GPI-anchor could inhibit the production of infectious HIV-1 and render virions sensitive to complement attack [1]. Therefore, changes in the "GPI-anchor" pathway might promote the spread of EV-A71 and CV-A16.…”
Section: Discussionmentioning
confidence: 99%
“…Among these pathways, the GPI-anchor is considered to play an important role in the infection and pathogenesis of many viruses. Amet et al demonstrated that the deficiency of GPI-anchor could attenuate the production of infectious HIV-1 and render virions sensitive to complement attack [24]. Therefore, changes in the "GPI-anchor" pathway might promote the spread of EV-A71 and CV-A16 virus.…”
Section: Discussionmentioning
confidence: 99%